TELIDON, THE CANADIAN VIDEOTEX SYSTEM, AND ITS IMPLICATIONS FOR INFORMATION SCIENCE - Phillips, Dorothy A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF